2023
DOI: 10.22460/infinity.v12i1.p41-54
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Online Learning and Its Impact on Learning Achievements of Mathematics Education Students

Abstract: Implementing online learning in a higher education environment requires an analysis of learning outcomes and their impact on students, lecturers, and the institutions that administer the learning. The implementation of online learning shows that the learning process takes place and the readiness of lecturers and students to implement online learning. The impact given by online learning is in the form of GPA and student perceptions of the learning process they experience. Based on the research results, various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Courses have been designed to accommodate different types of technological support, allowing for both self-learning and interaction in both synchronous and asynchronous formats (Cirrulli, et al, 2016). As for online learning methods, they were divided into two types: synchronous and asynchronous (Panjaitan et al, 2023). Synchronous learning refers to real-time interaction between educators and students, typically through audio or video conferencing platforms.…”
Section: Asynchronous and Synchronous Learningmentioning
confidence: 99%
“…Courses have been designed to accommodate different types of technological support, allowing for both self-learning and interaction in both synchronous and asynchronous formats (Cirrulli, et al, 2016). As for online learning methods, they were divided into two types: synchronous and asynchronous (Panjaitan et al, 2023). Synchronous learning refers to real-time interaction between educators and students, typically through audio or video conferencing platforms.…”
Section: Asynchronous and Synchronous Learningmentioning
confidence: 99%
“…Based on these cases, several previous studies have shown the impact of teachers' unskillness in teaching mathematics online, some of the impacts include low motivation and achievement of students' mathematics learning (Panjaitan et al, 2023;Sujadi et al, 2022).…”
Section: Introductionmentioning
confidence: 98%
“…On the one hand, online learning makes mathematics learning flexible (Hendriana et al, 2019;Panjaitan et al, 2023). On the other hand, this learning model has limitations regarding location, space, and time, as not all students have equal access to any or all aspects of the online learning process (Aisyah & Murniati, 2022;Cooper, 2006).…”
Section: Introductionmentioning
confidence: 99%